The impact of firm financing constraints on R&D over the business cycle - Männasoo, Kadri; Meriküll, Jaanika (IOS working papers, 2015)
The paper studies financing constraints for R&D over the latest boom and bust episode in Central and Eastern Europe (CEE). Given that financial and venture capital markets in CEE are thin in comparison to those in high-income economies and that many of CEE countries experienced a credit crunch during the last recession, it is proposed that financing constraints have a significant adverse effect on R&D activity in these countries. The paper uses two complementary firm-level data-sources from ten CEE countries. The results suggest that the role of financing constraints for R&D expenditures in CEE countries is substantial, as the probability of credit constrained firms undertaking R&D activities is around 70% lower and firms' R&D expenditure cash flow sensitivity is very high. Despite the severity of the crisis, the adverse effect of financing constraints for R&D did not increase in the financial crisis. It is also confirmed that, conditional on credit constraints, firms' R&D activity is higher in a recession.